Hydroxychloroquine is associated with lower platelet activity and improved vascular health in systemic lupus erythematosus - Peter Izmirly; H Michael Belmont; Jill P Buyon; MacIntosh Grant Cornwell; Elliot S Luttrell-Williams; Michael Golpanian; Hanane El Bannoudi; Khrystyna Myndzar; Stuart Katz; Nathaniel R Smilowitz; Alexis Engel; Robert Clancy; et al. (Lupus Science and Medicine)
Objective Hydroxychloroquine (HCQ) is a mainstay of therapy in the treatment of SLE. The effect of HCQ on platelets and vascular health is uncertain. We investigated the relationship between HCQ use and dose with platelet activity, platelet transcriptomics and vascular health in patients with SLE.Methods Platelet aggregation, platelet mRNA expression and vascular health (sublingual capillary perfused boundary region (PBR), red blood cell filling (RBCF) and brachial artery reactivity testing) were analysed by HCQ use and dose.Results Among 132 subjects with SLE (age: 39.7±12.9 years, 97% female), 108 were on HCQ. SLE disease activity was similar between subjects on and off HCQ. Platelet aggregation in response to multiple agonists was significantly lower in patients on HCQ. There were inverse relationships between HCQ dose and gene expression pathways of platelet activity. Gene expression of P-selectin (SELP) was inversely correlated with HCQ dose (r=−0.41, p=0.003), which was validated at the protein level. Subjects on HCQ had improved vascular function correlating with HCQ dose as measured by lower PBR (r=−0.52, p=0.007), higher RBCF (r=0.55, p=0.004) and greater brachial artery reactivity (r=0.43, p=0.056).Conclusion HCQ use was associated with decreased platelet activation and activation-related transcripts and improved vascular health in SLE.